Correlation between people with a creative mentality and their propensity to make lucrative investing choices in contrast to those who only depend on financial resources - Ullah, Khalil (Asian Journal of Logistics Management, 2025)
This study examines whether creative individuals can make more profitable investment decisions than those who rely on financial resources alone. Using Excel to analyze survey data, the research study utilized Pearson correlation and multiple regression analyses to test the hypothesis that creativity is positively related to investment outcomes.Results have shown that the respondents were moderately oriented toward profitable investments, as evidenced by an average of 3.23 and a standard deviation of 0.925. The level of creativity was also moderate and averaged 3.95. The skewed results to the right suggest that only a small share of the respondents were highly disposed toward profitable decisions.This research underlines the creativity of investment strategies and their potential to enhance decision-making processes. However, limitations remain, especially in the reliance on literature and case studies, suggesting that future research should further explore the nuances of creativity in investment performance.The practical implications of this study may enable individuals and organizations to enhance financial outcomes through the integration of creative thinking in investment strategies that eventually engender informed decision-making and financial stability across diversities